Perceptions of the Police by LGBT Communities - Owen, Stephen S. (American journal of criminal justice, 2018)
The purpose of this study is to explore how lesbian, gay, bisexual, and transgender (LGBT) communities perceive the police. Historically, relationships between LGBT communities and the police have been strained due to a legacy of discriminatory actions, although some police agencies have more recently taken steps to build relationships with LGBT communities. A survey was administered to a sample of LGBT and heterosexual respondents ( n = 787) to measure perceptions regarding police fairness, policing qualities, policing outcomes, and police interactions with LGBT communities. Across a number of measures and scales, the perceptions of LGBT participants were significantly more negative than those of other participants, including when the variables of race, income, location type (e.g., rural, small town, suburban, urban), prior service as a police officer, and quality of prior interactions with the police, are controlled in multivariate modeling. Implications for police training and policy are discussed, as well as theoretical contexts that frame the results.